Ikatan Patron-Klien dalam Pertanian Kopi: Peran Toke dalam Kesejahteraan Petani - Lestari, Iga; Nurdin, Ibnu Phonna (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2025)
Human life is inherently shaped by social interactions, and this is particularly evident in agricultural activities, where coffee farmers are closely linked to social relationships with toke (middlemen). In the context of coffee farming, farmers establish cooperative relationships with toke to market their crops. Additionally, farmers rely on various natural resources essential for sustaining their agricultural activities. Over time, this interaction evolves into a patron-client bond. This study aims to analyze and describe the development of patron-client relationships between coffee farmers in Panji Mulia I Village, Bukit District, Bener Meriah Regency. The research utilizes a descriptive qualitative approach, employing fieldwork to collect data. Methods of data collection included observations, interviews, and documentation, with purposive sampling techniques used to select the informants. The theoretical framework applied in this research is James C. Scott's Patron-Client theory. The findings indicate that the five forms of patron-to-client flows provided by toke to farmers include: basic subsistence livelihood, crisis subsistence guarantee, protection, brokerage and influence, and collective patron services. Furthermore, there is also a flow from clients to patrons, with farmers offering labor and expertise in support of toke’s activities. In conclusion, the patron-client relationship between toke and coffee farmers in Panji Mulia I Village is collaborative. This relationship creates a reciprocal bond that benefits both parties, built upon mutual trust and loyalty.